Guiding Transition Metal‐Doped Hollow Cerium Tandem Nanozymes with Elaborately Regulated Multi‐Enzymatic Activities for Intensive Chemodynamic Therapy. Issue 7 (9th January 2022) - Dong, Shuming; Dong, Yushan; Liu, Bin; Liu, Jing; Liu, Shikai; Zhao, Zhiyu; Li, Wenting; Tian, Boshi; Zhao, Ruoxi; He, Fei; Gai, Shili; Xie, Ying; et al.
Abstract: Clinical applications of nanozyme‐initiated chemodynamic therapy (NCDT) have been severely limited by the poor catalytic efficiency of nanozymes, insufficient endogenous hydrogen peroxide (H2 O2 ) content, and its off‐target consumption. Herein, the authors developed a hollow mesoporous Mn/Zr‐co‐doped CeO2 tandem nanozyme (PHMZCO‐AT) with regulated multi‐enzymatic activities, that is, the enhancement of superoxide dismutase (SOD)‐like and peroxidase (POD)‐like activities and inhibition of catalase (CAT)‐like activity. PHMZCO‐AT as a H2 O2 homeostasis disruptor promotes H2 O2 evolution and restrains off‐target elimination of H2 O2 to achieve intensive NCDT. PHMZCO‐AT with SOD‐like activity catalyzes endogenous superoxide anion (O2 − ) into H2 O2 in the tumor region. The suppression of CAT activity and depletion of glutathione by PHMZCO‐AT largely weaken the off‐target decomposition of H2 O2 to H2 O. Elevated H2 O2 is then catalyzed by the downstream POD‐like activity of PHMZCO‐AT to generate toxic hydroxyl radicals, further inducing tumor apoptosis and death. T 1 ‐weighted magnetic resonance imaging and X‐ray computed tomography imaging are also achieved using PHMZCO‐AT due to the existence of paramagnetic Mn 2+ and the high X‐ray attenuation ability of elemental Zr, permitting in vivo tracking of the therapeutic process. This work presents a typical paradigm to achieve intensive NCDT efficacy by regulating multi‐enzymatic activities of nanozymes to perturb the H2 O2 homeostasis. Abstract : A hollow mesoporous Mn/Zr‐co‐doped CeO2 tandem nanozyme is developed, serving as an H2 O2 homeostasis disruptor to promote H2 O2 evolvement, restrain the off‐target elimination of H2 O2, and realize intensive nanozyme‐initiated chemodynamic therapy of tumor. T 1 ‐weighted magnetic resonance imaging and high‐contrast X‐ray computed tomography imaging are also achieved using the nanozyme for in vivo tracking of the therapeutic process.